1999
DOI: 10.1136/emj.16.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate ambulance usage is a retrospective diagnosis.

Abstract: Letters, CD-ROM review 75 better if we are to proactively manage this demand to the benefit of the patient, the ambulance service, and the wider NHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Another factor affecting the retrospective method of determining urgency is that if the patient is transported to hospital by ambulance, the treatment provided by paramedics may have improved the patient's condition before arrival at the ED, and therefore these cases will be at a lower triage level on arrival than they were at the time of symptom presentation. 22 Similarly, the evaluation of patient adherence to telephone triage recommendations in Western Australia 23 identified that adherence is dependent on symptom presentation.…”
Section: Retrospective V Prospective Case Definition and Analysismentioning
confidence: 99%
“…Another factor affecting the retrospective method of determining urgency is that if the patient is transported to hospital by ambulance, the treatment provided by paramedics may have improved the patient's condition before arrival at the ED, and therefore these cases will be at a lower triage level on arrival than they were at the time of symptom presentation. 22 Similarly, the evaluation of patient adherence to telephone triage recommendations in Western Australia 23 identified that adherence is dependent on symptom presentation.…”
Section: Retrospective V Prospective Case Definition and Analysismentioning
confidence: 99%